Impact of intervention strategies on fruit and vegetable intake in low-, middle- and high-income countries: A scoping review - Koyratty, Nadia; Azupogo, Fusta; Smith, Taryn J.; Hinnouho, Guy-Marino; Tharaney, Manisha; Bliznashka, Lilia; Olney, Deanna K.; Hess, Sonja Y. (SAGE Publications, 2025)
Background: Despite well-documented health benefits, fruit and vegetable (F&V) intake remains below recommended levels globally.